Identity Politics: Anthropological Perspectives on Quilombolas Rights and Racial Quotas - Hofbauer, Andreas [UNESP] (Ecole Hautes Etudes & Sci Soc, Centre Recherches Bresil Contemp, 2016)
Proposals to implement targeted policies aimed at combatting the effects of racial discrimination in Brazil have provoked great controversy in Brazilian society. In this debate, the perspectives and contributions of Brazilian anthropologists, both in defense and in interrogation of these identity politics, have been widely commented upon. This article proposes to analyze these policies using the examples of two emblematic cases: that of the rights guaranteed by the Constitution to the remnants of maroon communities (quilombos) and that of the implementation of racial quotas in public universities. Special attention is given to the way in which paradigmatic concepts in anthropological thought - race, cultural, identity (ethnicity) - are mobilized in these respective lines of argument.
Keywords: identity politics; quilombo; racial quotas; difference and inequality; anthropological theory; Brazil